Microorganism-Driven 2,4-D Biodegradation: Current Status and Emerging Opportunities - Chen, Shao-Fang; Chen, Wen-Juan; Song, Haoran; Liu, Mingqiu; Mishra, Sandhya; Ghorab, Mohamed A.; Chen, Shaohua; Chang, Changqing (Molecules (Basel, Switzerland), 2024)
The herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) has been widely used around the world in both agricultural and non-agricultural fields due to its high activity. However, the heavy use of 2,4-D has resulted in serious environmental contamination, posing a significant risk to non-target organisms, including human beings. This has raised substantial concerns regarding its impact. In addition to agricultural use, accidental spills of 2,4-D can pose serious threats to human health and the ecosystem, emphasizing the importance of prompt pollution remediation. A variety of technologies have been developed to remove 2,4-D residues from the environment, such as incineration, adsorption, ozonation, photodegradation, the photo-Fenton process, and microbial degradation. Compared with traditional physical and chemical remediation methods, microorganisms are the most effective way to remediate 2,4-D pollution because of their rich species, wide distribution, and diverse metabolic pathways. Numerous studies demonstrate that the degradation of 2,4-D in the environment is primarily driven by enzymatic processes carried out by soil microorganisms. To date, a number of bacterial and fungal strains associated with 2,4-D biodegradation have been isolated, such as Sphingomonas, Pseudomonas, Cupriavidus, Achromobacter, Ochrobactrum, Mortierella, and Umbelopsis. Moreover, several key enzymes and genes responsible for 2,4-D biodegradation are also being identified. However, further in-depth research based on multi-omics is needed to elaborate their role in the evolution of novel catabolic pathways and the microbial degradation of 2,4-D. Here, this review provides a comprehensive analysis of recent progress on elucidating the degradation mechanisms of the herbicide 2,4-D, including the microbial strains responsible for its degradation, the enzymes participating in its degradation, and the associated genetic components. Furthermore, it explores the complex biochemical pathways and molecular mechanisms involved in the biodegradation of 2,4-D. In addition, molecular docking techniques are employed to identify crucial amino acids within an alpha-ketoglutarate-dependent 2,4-D dioxygenase that interacts with 2,4-D, thereby offering valuable insights that can inform the development of effective strategies for the biological remediation of this herbicide.